Seed viability test for six Philippine beach forest plant species found in Taklong Island, Nueva Valencia, Guimaras - Jalandoni, Ryan Sherwin D.
Beach forest species are now gaining popularity due to their role in protecting coastal areas in the country. However, little information is available on how to grow and propagate them, therefore studies focusing on propagation of beach forest is needed. This study aimed to (1) evaluate the seed germination rate of each plant species, and (2) compare their germination rates with each other. Seeds of Abrus precatorius, Caesalpinia sappan, Guettarda speciosa, Guilandina bonduc, Mucuna pruriens, and Sophora tomentosa were taken from Taklong Island, Nueva Valencia, Guimaras, Philippines. The seeds were then pretreated and assed using seed germination test for 30 days. Results showed that G. bonduc and M. puriens have germination rates, of 56% and 51% respectively, which is relatively higher than that of Abrus precatorius, Caesalpinia sappan, Guettarda speciosa, and Sophora tomentosa that have germination rates of 13%, 3%, 9% and 16% respectively. It can be implied that the six species have low seed viability. Therefore, it is recommended to conduct future studies on enhancing the seed germination rates of the six species.